Wear of a Fe2.5Ni2.5CrAl multiprincipal element alloy: a combined experimental and molecular dynamics study - Qiao, Ling (2023)
The Fe2.5Ni2.5CrAl multiprincipal element alloy (MPEA) is a promising material for engineering applications because of its high strength and plasticity values. To evaluate the friction and wear performance, reciprocating dry sliding tests and molecular dynamics (MD) simulations are performed to determine the wear mechanism over a range of length scales. This alloy exhibits a lower average friction coefficient and wear volume loss during dry sliding compared with the well-known Fe2Ni2CrAl alloy. The worn surface morphology reveals abrasive scratches, grooves, and delamination. The fine wear debris possesses high oxygen content, leading to higher wear resistance. The wear mechanism involves abrasive, adhesive, and oxidative wear. The wear, atomic stress and shear strain, dislocations, and lattice structure are analyzed by MD simulations. Point defects, atomic clusters, and stacking faults are identified in the nanowear process. The behavior of the (Formula presented.) (Shockley)-type dislocations is identified as the main dislocation mechanism during sliding. Stacking faults produced during the stress release process are present in the indentation. This work provides a deep insight into the friction and wear behavior of Fe2.5Ni2.5CrAl MPEAs.